2016
DOI: 10.4137/cment.s40364
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette: Role in the Primary Prevention of Oral Cavity Cancer

Abstract: BACKGROUNDCigarette smoke has been identified as the main cause of oral cavity carcinoma. Recently, the electronic cigarette, a battery-operated device, was developed to help smokers stop their tobacco addiction. This study aimed to evaluate the safety of electronic cigarettes and to establish the possible role of such device in the primary prevention of oral cavity cancer.SUBJECTS AND METHODSThis study included 65 subjects who were divided into three groups (smokers, e-cigarette smokers, and nonsmokers). All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 33 publications
1
57
0
8
Order By: Relevance
“…To evaluate the prevalence of cellular changes in the oral mucosa in traditional cigarette smokers and e-cigs users, in comparison with nonsmokers, scrapings of the oral mucosa from the three groups of participants (smokers, e-cig smokers, and nonsmokers) were cytologically examined using micronucleus assay test which is a cytological method that has been used to assess OSCC risk in smokers or generally, in subjects exposed to carcinogens [81]. The prevalence of micronuclei in oral cavity cells exhibited a statistically significant decrease in e-cigs users similar to those of controls, compared to that in the smokers group, based on the average total number of micronucleated cells/1000 cells and the average total number of micronuclei/1000 cells values.…”
Section: Studies On Direct Health Effects Of Ends In the Oral Cavitymentioning
confidence: 99%
“…To evaluate the prevalence of cellular changes in the oral mucosa in traditional cigarette smokers and e-cigs users, in comparison with nonsmokers, scrapings of the oral mucosa from the three groups of participants (smokers, e-cig smokers, and nonsmokers) were cytologically examined using micronucleus assay test which is a cytological method that has been used to assess OSCC risk in smokers or generally, in subjects exposed to carcinogens [81]. The prevalence of micronuclei in oral cavity cells exhibited a statistically significant decrease in e-cigs users similar to those of controls, compared to that in the smokers group, based on the average total number of micronucleated cells/1000 cells and the average total number of micronuclei/1000 cells values.…”
Section: Studies On Direct Health Effects Of Ends In the Oral Cavitymentioning
confidence: 99%
“…3 Acute and chronic tobacco cigarette smoking have been shown to increase white blood cell count, cause low grade inflammation, increase the load of inflammatory cytokines, and cause oral mucosal changes; however, these effects are not seen with ecigarettes. 3,4 In accordance with this improved safety, the use of e-cigarettes has been increasing. From 2014 to 2015, there was a 14% overall growth in e-cigarettes based on sales data.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, electronic cigarettes (e‐cigarettes), which typically do not contain these additives but offer comparable levels of nicotine and a similar user experience, have been suggested as less risky alternatives . Acute and chronic tobacco cigarette smoking have been shown to increase white blood cell count, cause low grade inflammation, increase the load of inflammatory cytokines, and cause oral mucosal changes; however, these effects are not seen with e‐cigarettes …”
Section: Introductionmentioning
confidence: 99%
“…There have been few studies that address the direct health effect of EC smoking, especially regarding the oral mucosa. A recent study [9] based on cytological examination of scrapings from the oral mucosa in three groups of patients (smokers, ECs smokers, and non-smokers) demonstrated that there were no statistically significant differences in the micronuclei distribution, suggesting that the use of ECs seems to be safe for oral cells. On the other hand, Reuther et al [10] found that ECs may have an effect on the blood flow (measured using a laser Doppler) of the oral mucosa.…”
Section: Resultsmentioning
confidence: 98%